Empathy for a Black Woman Victim of Police Sexual Violence: The Roles of Crime-Related Stress and Stereotype Attributions - Johnson, James (Journal of interpersonal violence, 2023)
Police sexual violence has been ranked as the second most common form of misconduct among police officers. Moreover, there is evidence that Black women are at heightened risk of being victims of such police violence. A report titled Say Her Name: Resisting Police Brutality Against Black Women has brought international attention to the minimal empirical focus on such police violence toward Black women. To address this lacuna in the literature, using an incident of police sexual assault of a woman, we assessed whether victim’s race and participants’ level of crime-related stress (i.e., stress due to crime victimization) would influence empathic responding toward the victim. Prolific participants (N = 411) first completed a measure of crime-related stress. They then read an article describing a White police officer’s sexual assault of a Black or White woman. Next, participants completed a racial stereotype-related measure (i.e., Black women’s higher sexual proclivity) and a stereotype-unrelated measure (i.e., perceived victim untrustworthiness), and reported their victim-directed empathic responding. At high stress levels, participants reported less empathy for the Black (relative to White) victim. At low stress levels, there was greater Black victim-directed empathy. The race effects on empathy were mediated by heightened attribution of Black women-related stereotypical beliefs to the Black victim at high stress levels and by diminished attribution at low stress levels. In sum, we addressed the lacuna in the literature on police sexual violence against Black women while providing evidence that stress can play a critical role in the occurrence of the oft-cited outgroup-directed empathy deficit.